LITERATURE ANALYSIS OF THE INFLUENCE OF SOCIAL MEDIA ON ACADEMIC ACHIEVEMENT - I'tiqafah, Alisya; Alia Putri, Nayma; Maharani, Olivia; Alrefi, Alrefi (Program Studi Bimbingan dan Konseling FKIP UNJA, 2025)
The use of social media is very difficult to separate its use in individuals including students. Not only adults but, students have also begun to use social media as an additional medium in making it easier for them to find learning resources through social media. However, not only the positive impact offered by social media, the negative impact of social media is also offered to social media lovers. The purpose of this study is to determine the impact of social media use on student academic achievement. This research uses a literature study method or relevant data such as journals related to the influence of social media on student academic achievement. The results of this study are, the use of social media on each student has a positive impact and a negative impact depending on how students continue to use social media. Parents and teachers also play an important role in guiding and also supervising students in the use of social media, so that students can benefit from using social media. if not directed and supervised, the negative impact will be obtained by students.